Resilience as a Resource for Overcoming Negative Impacts of Volunteering - Barinov, Sergey (Psychological Counseling and Psychotherapy, 2025)
The aim of the study to determine the specifics of resilience as a resource for volunteer activities.  Analysis of foreign theoretical models of resilience shows that this phenomenon is considered as a multidimensional, dynamic process in which personal, social, cognitive and contextual factors interact. Domestic psychological science actively integrates these global approaches, adapting them to the realities of modern Ukraine. This has made it possible to form a number of conceptual and empirical directions aimed at studying the resilience of the individual in conditions of uncertainty and crisis challenges. The generalization of modern domestic research shows that resilience in Ukrainian psychology is considered as a systemic, multi-level quality that ensures effective adaptation, self-regulation and restoration of the personality in conditions of stress and crisis influences. The article shows that scientists are consistently expanding the understanding of this phenomenon - from a separate resource to a universal ability to maintain mental balance and vitality. It also was shown that Ukrainian research reveals similar trends, demonstrating that volunteer activity contributes to the formation of moral values, social maturity, empathy, a sense of responsibility, but at the same time can be accompanied by emotional exhaustion, secondary traumatization and professional burnout. This necessitates the development of psychological resources of resilience of volunteers. In this context, the phenomenon of resilience acquires special importance, which appears as a dynamic mechanism for maintaining adaptive functioning in conditions of stress. We concluded that various theoretical models prove that resilience is formed in the interaction of individual, social and contextual factors and can be developed through psychological preparation, self-regulation training and social support. Therefore, volunteering in crisis conditions requires a high level of resilience as a basic resource for overcoming stress, maintaining mental health and ensuring the effectiveness of assistance.